2022
DOI: 10.3389/fnut.2022.974443
|View full text |Cite
|
Sign up to set email alerts
|

Dietary metal intake and the prevalence of erectile dysfunction in US men: Results from National Health and Nutrition Examination Survey 2001–2004

Abstract: BackgroundErectile dysfunction (ED) mainly affects men over 40 years of age and is a common clinical condition. In addition to hypertension and diabetes, environment, and lifestyle are also significantly associated with erectile dysfunction. The relationship between dietary trace metal intake and ED has not been studied.Materials and methodsData on participants were obtained from the National Health and Nutrition Examination Survey for this study, and those with incomplete information on clinical variables wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In a cross-sectional study involving 134 ED patients and 50 healthy controls, Jiangnan reported a greater prevalence of low blood levels of folic acid and vitamin B12 among ED patients than among control individuals 49 . Similarly, Liu's study of 3745 adult males in the U.S. revealed a link between ED risk and the intake of antioxidants such as magnesium, zinc, copper, and selenium 50 . However, these studies did not fully consider the influence of prooxidants or the synergistic effects of antioxidants within biological systems 51 .…”
Section: Discussionmentioning
confidence: 94%
“…In a cross-sectional study involving 134 ED patients and 50 healthy controls, Jiangnan reported a greater prevalence of low blood levels of folic acid and vitamin B12 among ED patients than among control individuals 49 . Similarly, Liu's study of 3745 adult males in the U.S. revealed a link between ED risk and the intake of antioxidants such as magnesium, zinc, copper, and selenium 50 . However, these studies did not fully consider the influence of prooxidants or the synergistic effects of antioxidants within biological systems 51 .…”
Section: Discussionmentioning
confidence: 94%
“…Trace metals actively participate in averting vascular damage and atherosclerosis through various pathways, thereby safeguarding the relatively narrow-diameter penile arteries. Existing studies (including multiple animal studies) propose that adhering to recommended dietary metal intake limits may prove advantageous in reducing the prevalence of erectile dysfunction, although research on the correlation between dietary metal intake and ED prevalence remains limited [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cu actively participates in nitric oxide production, a compound that facilitates blood vessel relaxation and increased blood flow to the penis. Inadequate Cu levels may impede nitric oxide production, resulting in reduced blood flow and difficulties in achieving or maintaining an erection [4].…”
Section: Introductionmentioning
confidence: 99%